Magnetic resonance spectroscopy in Alzheimer’s disease - Graff-Radford J (Dove Medical Press, 2013)
Jonathan Graff-Radford,1 Kejal Kantarci21Department of Neurology, 2Department of Radiology, Mayo Clinic, Rochester, MN, USAAbstract: Aging is the primary risk factor for dementia. With increasing life expectancy and aging populations worldwide, dementia is becoming one of the significant public health problems of the century. The most common pathology underlying dementia in older adults is Alzheimer’s disease. Proton magnetic resonance spectroscopy (MRS) may provide a window into the biochemical changes associated with the loss of neuronal integrity and other neurodegenerative pathology that involve the brain before the manifestations of cognitive impairment in patients who are at risk for Alzheimer’s disease. This review focuses on proton MRS studies in normal aging, mild cognitive impairment, and dementia, and how proton MRS metabolite levels may be potential biomarkers for early diagnosis of dementia-related pathologic changes in the brain.Keywords: Alzheimer’s disease, magnetic resonance spectroscopy, mild cognitive impairment